An updated analysis of housing price determinants in Singapore: implications for policy and planning - Ang, Qi Jian (Nanyang Technological University, 2023)
Housing prices in Singapore have risen over the past two decades, and was further amplified during the Covid-19 pandemic. This paper seeks to provide a more updated analysis of housing price determinants in the private and public housing market, incorporating factors such as macroeconomic variables, supply, demographic variables, and the Covid-19 pandemic. We constructed a multivariate OLS regression model to analyze data between 2000 and 2022. We found that income, inflation, exchange rate, and money supply are crucial drivers of housing prices in both markets. The two housing markets are interrelated, and supply-side and demographic factors do drive housing prices. Interestingly, we found that the Covid-19 pandemic had a significant impact on private housing prices but not for public housing. The analysis was extended to explore the price differences between different regions for private housing. Private housing in the outer central and rest of central regions rose during the pandemic, while the core central region experienced a decrease. Our findings affirm the importance of existing property cooling measures, and highlight key factors such as new housing supply, the relationship between both housing markets and demographic trends as important considerations for policymakers when designing housing policies.